2020
DOI: 10.14267/retp2020.02.20
|View full text |Cite
|
Sign up to set email alerts
|

A vállalati társadalmi teljesítmény rövid távú hatásai a pénzügyi jövedelmezőségre = The Short-term Effects of Corporate Social Performance on Financial Profitability

Abstract: KÖZ-GAZDASÁG 2020/2 164 2018 company-level data and performed on a 1,099-element firm sample from the MSCI ACWI Index. Regression calculations rest on the weighted least squares (WLS) method.The dependent variable is the return on sales (ROS, 2018); the control variables are previous year (2017) profitability, size, leverage, growth, capital intensity, industry and regional dummies. The empirical results show that higher ESG, E, and S ratings do not change profitability significantly in the short run. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Certain studies, however, have not found a clear and long-term connection between yields and responsible corporate management (Gillian-Starks, 2017). Fain (2020) has come to a mixed result regarding the connection between the financial performance and ESG score of a company. While a higher E, S and ESG rating had no significant impact on financial performance, a 10-point increase of the governance factor (G) resulted in 0.3% improvement of the after-tax return on sales.…”
Section: Introductionmentioning
confidence: 99%
“…Certain studies, however, have not found a clear and long-term connection between yields and responsible corporate management (Gillian-Starks, 2017). Fain (2020) has come to a mixed result regarding the connection between the financial performance and ESG score of a company. While a higher E, S and ESG rating had no significant impact on financial performance, a 10-point increase of the governance factor (G) resulted in 0.3% improvement of the after-tax return on sales.…”
Section: Introductionmentioning
confidence: 99%